British Imperialism and the Political Economy of Malayan Independence. Issue 3 (3rd May 2016) - Sutton, Alex
ABSTRACT: The article focuses on Britain's relationship with Malaya shortly before and after its independence from the British Empire. The article looks at the negotiations concerning the financial settlement prior to independence. Britain sought to keep Malaya within the sterling area at all costs, even after de jure convertibility had been achieved, due to its high dollar earning capacity, which remained important due to persistent trade deficits with the US from the end of the Second World War. The article argues that this settlement, while seemingly very generous for an independent Malaya, was still very much intended to maintain Britain's role within the global economy, to ensure sterling's status as an international currency and to support conditions for British economic growth.